Appraising the role of memorable tourism experience between the relationship of destination image and Melaka domestic tourists’ revisit intention / Shakira Izzati Johari and Nor Asmalina Mohd Anuar - Johari, Shakira Izzati; Mohd Anuar, Nor Asmalina (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Cawangan Selangor, 2020)
The actual nature of tourism experience is mainly associated with delivering satisfaction to tourists. However, the concept of tourism experience has been continuously developed and is going beyond purveying tourist satisfaction as time passes by. This is in line with the concept of memorable tourism experience that is now gaining traction. Melaka was chosen as setting of the study due to competition from other destinations that have received UNESCO recognition such as Cambodia, Myanmar and Indonesia. As compared to Melaka, these destinations recorded higher growth rate of tourist arrivals. Therefore, it is imperative to understand how Melaka’s image can contribute to positive memorable experience that can increase domestic tourist arrivals. This study seeks to examine the influence of destination image on tourists’ revisit intention with the mediating role of memorable tourism experience. Questionnaires were distributed to domestic tourists in Melaka through the convenient sampling method. This study reveals that both cognitive and affective components of destination image have positively influence domestic tourists’ revisit intention to Melaka. Memorable tourism experience was also found to mediate this relationship. On top of contributing to the body of knowledge, the finding of this study is expected to help destination managers in developing measures to maintain or enrich the image of Melaka.